Review of the genus Hannemania (Acari: Leeuwenhoekiidae) with description the two new species in amphibians from Chile - Fuente, M. C. Silva-De La; Moreno-Salas, L.; Castro-Carrasco, C. (Zootaxa, 2016)
The genus Hannemania includes 25 species of parasites of amphibians; Chile has one species: H. pattoni Sambon, 1928. This work reviews the genus Hannemania and describes two new species from Chile: Hannemania ortizi sp. nov., a parasite of Pleurodema thaul (Lesson) (Anura: Leptodactylidae) and Eupsophus contulmoensis Ortiz, Ibarra-Vidal, Formas (Anura: Alsodidae) and Hannemania gonzaleacunae sp. nov., a parasite of E. nahuelbutensis Ortiz and Ibarra-Vidal (Anura: Alsodidae). The new species differ from H. pattoni and other nearby species principally by character states of the palp and leg setae. A comparison of the diagnostic characters for all species of Hannemania is included.